FAEYA Collection / Nur Syamimi Mohd Samsul - Mohd Samsul, Nur Syamimi (2021)
In line with its mission and vision, FAEYA Collection wants every woman to feel hijab fashion with a stylish style. FAEYA Collection offers "Bawal Cotton Premium" which has a variety of design patterns and a variety of colors available. the price given is very affordable, a piece is only RM 15 ringgit. This product is targeted at women to buy it regardless of students, housewives or working women, but for men can also buy it to gift this product to special people. a very reasonable price offer can attract customers to buy this product. the owner of this FAEYA Collection is Nurul Fatira Binti Roslan. I created a Facebook (FB) page to further expand her online business. besides that I can also learn online sales. I also learned to edit images to advertise the products I want to sell.